ChemInform Abstract: Role of AMP‐Activated Protein Kinase in Cancer Therapy. Issue 36 (9th September 2014) - Rehman, Gauhar; Shehzad, Adeeb; Khan, Abdul Latif; Hamayun, Muhammad
Abstract Review: 133 refs.